Отримання заряджених полісульфонієвих ультрафільтраційних мембран та вивчення їх властивостей - Босак, В.З.; Вакулюк, П.В.; Бурбан, А.Ф.; Антонюк, Н.Г.; Ісаєв, С.Д.; Лаврик, В.І. (Видавничий дім "Академперіодика" НАН України, 2007)
We have got the charged membranes and explored their properties. The method of chloromethylation of the surface of polysulfone membranes by grafting the functional group (–CH2Cl) with a subsequent treatment with triethylamine and sodium sulfite has been developed. It is established that the rejection coefficient of modified membranes relative to polyethylene glycol, albumin, and humic acids from their water solutions substantially depends on the chemical nature of the membrane surface.